Hubungan Usia dan Jenis Kelamin dengan Insiden Diabetes Melitus pada Masyarakat di Wilayah Kerja Puskesmas Jaya Baru Banda Aceh - Tamara Agustina; Khaira Rizki; Nurul Sakdah (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes Mellitus is a common non-communicable disease in the community and is now a global health problem with prevalence rates that continue to increase every year. Age and gender are thought to play a role in influencing the incidence of diabetes mellitus. This study aims to analyze the relationship between age and gender with the incidence of diabetes mellitus in the community in the Jaya Baru Health Center Work Area, Banda Aceh. The research design used was analytical with a cross-sectional approach. The population in this study amounted to 552 people, with a sample of 85 respondents obtained through the Proportional Random Sampling technique. The study was conducted in the Jaya Baru Health Center Work Area, Banda Aceh from May 3 to 15, 2025. Data analysis was carried out univariately and bivariately using the chi-square test. Data collection was carried out through questionnaires and random blood sugar level examinations. The results of the study showed a significant relationship between age and the incidence of diabetes mellitus (ρ-Value = 0.008), and there was no significant relationship between gender and the incidence of diabetes mellitus (ρ-Value = 0.650). In conclusion, there is a significant relationship between age and the incidence of diabetes mellitus, but there is no significant relationship between gender and the incidence of diabetes mellitus in the community in the Working Area of ​​the Jaya Baru Banda Aceh Health Center. It is hoped that the community will increase awareness of the importance of regular health checks, especially individuals in the at-risk age group and the more vulnerable gender.